Activation of intestinal epithelial Stat3 orchestrates tissue defense during gastrointestinal infection - Wittkopf, Nadine; Pickert, Geethanjali; Billmeier, Ulrike; Mahapatro, Mousumi; Wirtz, Stefan; Martini, Eva; Leppkes, Moritz; Neurath, Markus; Becker, Christoph (PLoS ONE, 2015)
Gastrointestinal infections with EHEC and EPEC are responsible for outbreaks of diarrheal diseases and represent a global health problem. Innate first-line-defense mechanisms such as production of mucus and antimicrobial peptides by intestinal epithelial cells are of utmost importance for host control of gastrointestinal infections. For the first time, we directly demonstrate a critical role for Stat3 activation in intestinal epithelial cells upon infection of mice with Citrobacter rodentium - a murine pathogen that mimics human infections with attaching and effacing Escherichia coli. C. rodentium induced transcription of IL-6 and IL-22 in gut samples of mice and was associated with activation of the transcription factor Stat3 in intestinal epithelial cells. C. rodentium infection induced expression of several antimicrobial peptides such as RegIII? and Pla2g2a in the intestine which was critically dependent on Stat3 activation. Consequently, mice with specific deletion of Stat3 in intestinal epithelial cells showed increased susceptibility to C. rodentium infection as indicated by high bacterial load, severe gut inflammation, pronounced intestinal epithelial cell death and dissemination of bacteria to distant organs. Together, our data implicate an essential role for Stat3 activation in intestinal epithelial cells during C. rodentium infection. Stat3 concerts the host response to bacterial infection by controlling bacterial growth and suppression of apoptosis to maintain intestinal epithelial barrier function.
EVALuna2:1990